2020
DOI: 10.1111/rec.13091
|View full text |Cite
|
Sign up to set email alerts
|

Detachment of Porites cylindrica nubbins by herbivorous fishes

Abstract: A form of active restoration for coral assemblages involves culturing coral nubbins at nursery sites before transplantation to recipient reefs. Incidental grazing and/or directed predation by local fish assemblages are major sources of dislodgement and mortality for coral nubbins in nurseries. However, the rate of coral nubbin detachment, how this varies across fish taxa, and whether nubbin size affects rates of detachment warrant further investigation. We used field and aquaria experiments to examine the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 58 publications
(83 reference statements)
4
3
0
Order By: Relevance
“…Differences in predation impacts on outplanted coral fragments between sites were also documented by Page, Muller & Vaughan (2018) in the Florida Keys. Similar to our findings, Quimpo, Cabaitan & Hoey (2019) suggested that coral outplants were more likely to be detached when outplanted onto reefs with higher biomass of herbivore and corallivore fishes in the Phillipines. Additionally, Quimpo, Cabaitan & Hoey (2019) reported that incidental grazing of herbivorous fish, particularly the parrotfish Chlorurus spilurus, were the main sources of coral detachment, but that the direct predation by corallivorous fishes only minimally affected coral outplants.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Differences in predation impacts on outplanted coral fragments between sites were also documented by Page, Muller & Vaughan (2018) in the Florida Keys. Similar to our findings, Quimpo, Cabaitan & Hoey (2019) suggested that coral outplants were more likely to be detached when outplanted onto reefs with higher biomass of herbivore and corallivore fishes in the Phillipines. Additionally, Quimpo, Cabaitan & Hoey (2019) reported that incidental grazing of herbivorous fish, particularly the parrotfish Chlorurus spilurus, were the main sources of coral detachment, but that the direct predation by corallivorous fishes only minimally affected coral outplants.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our findings, Quimpo, Cabaitan & Hoey (2019) suggested that coral outplants were more likely to be detached when outplanted onto reefs with higher biomass of herbivore and corallivore fishes in the Phillipines. Additionally, Quimpo, Cabaitan & Hoey (2019) reported that incidental grazing of herbivorous fish, particularly the parrotfish Chlorurus spilurus, were the main sources of coral detachment, but that the direct predation by corallivorous fishes only minimally affected coral outplants. Incidental fish predation was also observed by herbivorous fish removing algal tissue from nursery ropes in the Seychelles by Frias-Torres & Van de Geer (2015).…”
Section: Discussionsupporting
confidence: 90%
“…Differences in predation impacts on outplanted coral fragments between sites were also documented by Paige et al (2018) in the Florida Keys. Similar to our findings, Quimpo et al (2019) suggested that coral outplants were more likely to be detached when outplanted onto reefs with higher biomass of herbivore and corallivore fishes in the Phillipines. Additionally, Quimpo et al (2019) reported that incidental grazing of herbivorous fish, particularly the parrotfish Chlorurus spilurus, were the main sources of coral detachment, but that the direct predation by corallivorous fishes only minimally affected coral outplants.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our findings, Quimpo et al (2019) suggested that coral outplants were more likely to be detached when outplanted onto reefs with higher biomass of herbivore and corallivore fishes in the Phillipines. Additionally, Quimpo et al (2019) reported that incidental grazing of herbivorous fish, particularly the parrotfish Chlorurus spilurus, were the main sources of coral detachment, but that the direct predation by corallivorous fishes only minimally affected coral outplants. Incidental fish predation was also observed by herbivorous fish removing algal tissue from nursery ropes in the Seychelles by Frias-Torres and van de Geer (2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation